Problems of Economic Security in the Arctic Region - GOLUBEV, Sergei Sergeevich; SEKERIN, Vladimir Dmitriyevich; GOROKHOVA, Anna Evgenievna; BANK, Sergey Valeryevich (Journal of Environmental Management and Tourism, 2020)
The current problems and features of ensuring the economic security of the Arctic territories as part of national security are analyzed in the article. At the same time, economic security is of paramount importance, as it is the basis for the financing of other security measures. Specifics of the Arctic zone include its enormous resource and transport communication potential. The Arctic, most of which belongs to Russia, is rich in such types of strategic minerals as nickel, platinum, natural gas, diamonds, oil, etc. The economic risks of the Arctic zone are associated with its insufficient innovative potential and low competitiveness, high resource intensity and low efficiency of extractive activities, as well as underdeveloped infrastructure. The strategic areas of ensuring the economic security in the Arctic zone include improvement in the methods of state management of the Arctic region through the formation and implementation of state target programs and the transition of the Arctic economy to a new technological level. The modern aspects of the industry and technology development in the Arctic in the modern conditions of climate change are highlighted in the article. Special attention is paid to the formation and implementation of the interdepartmental integrated target program "Arctic technologies", as the article is based on the scientific results of its formation and implementation.